Nanotechnology-enabled materials for hemostatic and anti-infection treatments in orthopedic surgery - Sun H (Dove Medical Press, 2018)
Haolin Sun,1,2,* Lu Lv,3,* Yanjie Bai,4,* Huilin Yang,2,3 Huan Zhou,2,5 Chunde Li,1 Lei Yang2,3 1Department of Orthopaedics, Peking University First Hospital, Beijing 100034, China; 2International Research Center for Translational Orthopaedics (IRCTO), Soochow University, Suzhou 215006, China; 3Orthopaedic Institute and Department of Orthopaedics, Soochow University, Suzhou 215006, China; 4School of Public Health, Medical College, Soochow University, Suzhou 215000, China; 5School of Mechanical Engineering, Jiangsu University of Technology, Changzhou 213001, China *These authors contributed equally to this work Abstract: The hemostatic and anti-infection treatments in the field of orthopedics are always the pivotal yet challenging topics. In the first part of this review, synthesized or naturally derived nanoscale agents and materials for hemostatic treatment in orthopedic surgery are introduced. The hemostatic mechanisms and the safety concerns of these nanotechnology-enabled materials are discussed. Beside the materials to meet hemostatic needs in orthopedic surgery, the need for antimicrobial or anti-infection strategy in orthopedic surgery also becomes urgent. Nanosilver and its derivatives have the most consistent anti-infective effect and thus high translational potential for clinical applications. In the second part, the factors affecting the antimicrobial effect of nanosilver and its application status are summarized. Finally, the status and translational potential of various nanotechnology-enabled materials and agents for hemostatic and anti-infective treatments in orthopedic surgery are discussed. Keywords: nanotechnology, hemostatic, antimicrobial, orthopedic surgery